PERAN INOVASI DAN JARINGAN BISNIS TERHADAP KEBERHASILAN USAHA PADA MIXUE PEKALONGAN (PERSPEKTIF ETIKA BISNIS ISLAM) - Friza Rifqo Azizah; Ahmad Sukron (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the role of innovation and business networks in the success of Mixue Pekalongan from the perspective of Islamic business ethics. As a global beverage franchise, Mixue has experienced rapid growth in Indonesia, including in Pekalongan, where the majority of the population is Muslim. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. Key informants included the branch manager, employees, and consumers. The findings reveal that innovation includes regular product updates, digital marketing strategies via social media, and efficient, standardized operations. Meanwhile, the business network is supported through centralized supply distribution and cooperation among branches, which enhance operational efficiency and sustainability. The application of Islamic business ethics is reflected in honest transactions, fair treatment of employees, the use of halal-certified materials, and avoidance of usury and uncertainty in contracts. Mixue’s strength lies in its ability to integrate modern innovation with sharia principles, adding value in Muslim communities. The study concludes that innovation and business networks play a significant role in business success. It is recommended that branch offices be given more flexibility in local promotions and improved communication with headquarters. Future research may expand the scope to other branches to gain broader insight.